Treatment of Intracranial Pseudoaneurysms With a Novel Covered Stent: A Series of 19 Patients With Midterm Follow-Up - Wang, Wei; Liang, Xihong; Chen, Guangli; Yang, Peng; Zhang, Jialiang; Liu, Haocheng; Zhao, Shangfeng; Li, Yong; Sun, Bowen; Kang, Jun (Frontiers in Neurology, 2020)
Background The optimal treatment for intracranial pseudoaneurysm is unclear. This study aims to analyze the outcome of treating this disease with a novel covered stent. Materials and Methods The institutional imaging and clinical databases were retrospectively reviewed for patients with intracranial pseudoaneurysms treated with Willis covered stent from January 2017 to December 2019. The clinical presentations, etiology, intraoperative complications, and immediate and follow-up outcomes were analyzed. Results A total of 20 pseudoaneurysms in 19 patients were enrolled for analysis. 17 patients presented with vision loss and 2 with epistaxis. 19 Willis covered stent were deployed with one for each patient without technical failure. Intraoperative thrombosis was encountered in one patient (5.3%) and recanalized by tirofiban. During clinical follow-up, no further epistaxis occurred and visual acuity improved in 3 (17.6%) patients. Endoleak occurred in 7 (36.8%) patients after the initial balloon inflation and persisted in 1 (5.3%) patient after balloon re-inflation. This endoleak disappeared at an 8-month follow-up. At last angiographic follow-up (median 13 months), parent artery occlusion and in-stent stenosis occurred in 1 (5.3%) patient, respectively. No stent-related ischemic event was encountered. Conclusions Willis covered stent is feasible, safe, and efficient in treating intracranial pseudoaneurysms.